2017 impact estimation of exchange rate on foreign direct investment inflows and annual update of competitiveness analysis for 34 Greater China economies (World Scientific Publishing Company Pte Limited, 2019)
"This book is the fifth annual project of the Asia Competitiveness Institute studying competitiveness at the sub-national level of Greater China. ACI's flagship competitiveness study adopts a comprehensive framework to measure competitiveness by incorporating 102 indicators under four environments and 11 sub-environments. By undertaking the study at the sub-national level, it accounts for the considerable disparities within a large economy like Greater China. The study's unique methodology incorporates comparative strengths and weaknesses, and what-if policy simulations aimed at policy suggestions for each sub-national economy and region. A new feature of this competitiveness study introduces the concept of Shapley value for the assignment of weights to the various indicators that constitute competitiveness.